Comparative assesment of accuracy of IOPA and CBCT for maxillary molar furcation involvement: a clinical and radiological study - Parvez, Mohammed Fahad; Manjunath, Nandini; Kini, Raghavendra (International Journal of Research in Medical Sciences, 2018)
Background: Radiographs in periodontics will provide a two-dimensional image of a three-dimensional object and this leads to problems in terms of validity, accuracy and precision. Hence, the study was conducted with an aim to assess the accuracy of IOPA And CBCT for Maxillary Molar Furcation involvement by clinical and radiological methods. Methods: The study sample consisted of 17 subjects from the Out patient Department of A.J. Institute of Dental Science, Manglore belonging to both sexes and with age ranging from 35-55 years. The selected patients were those having presence of periodontal pockets of >5-6mm and advanced periodontal disease requiring surgical intervention. For the purpose of standardization, 3 sites of the maxillary first molars were assessed-Mid-buccal, Mesio-buccal, Disto-buccal. Iopa and CBCT measurements were taken which was followed by surgical intervention during which probing measurements were recorded. Statistical analysis was done using ‘unpaired t test’. Results: There was no statistically significant difference between CBCT measurements and surgical measurements (p≤0.05). Conclusions: CBCT accurately reproduced the clinical measurement of periodontal bone defects.